Chronic oral cannabidiol delays seizure onset and reduces seizure burden in a mouse model of CLN2 disease - Joshua T. Dearborn; Keigo Takahashi; Nicholas R. Rensing; Michael Wong; Jonathan D. Cooper; Mark S. Sands (PLoS ONE, 2026)
A growing body of literature describes the anti-inflammatory, neuroprotective, and anti-epileptic properties of the cannabis sativa constituent cannabidiol, suggesting that it might play a useful role in the treatment of neurodegenerative diseases. Late infantile neuronal ceroid lipofuscinosis (CLN2 disease) is a rare pediatric neurodegenerative disorder resulting from an inherited dysfunction of the lysosome. CLN2 disease, and its representative animal models, display neuroimmune response, neuroinflammation, neurodegeneration, and epileptic seizures, and these symptoms are all touted as potential targets of cannabidiol therapeutic benefit. Here, we treated a valid model of CLN2 disease with long-term daily cannabidiol (300 mg/kg) from 1 month of age until disease end stage and evaluated epileptic seizures, lifespan, and markers of neuroimmune response. Chronic cannabidiol treatment significantly delayed or fully eliminated seizures in CLN2 model mice compared to those treated with vehicle only, and the treatment led to a non-significant extension of lifespan. These effects occurred in the absence of any therapeutic benefit to physiological markers of disease such as GFAP, CD68, and cytokine/chemokine reactivity. Taken together, we show that chronic treatment with cannabidiol confers significant anti-seizure benefit to the mouse model of CLN2 disease, and that it does not appear to do so by altering the inflammatory and neuroimmune markers traditionally used to track CLN2 disease progression.